KEBUTUHAN RUANG TERBUKA HIJAU PADA KAWASAN PUSAT KOTA JAYAPURA - Baharuddin, Alfini (Bumi Lestari, 2011)
Jayapura downtown continues to growing very rapidly along the increasing of population, demand of land, and number of motor vehicles and it affects to the increasingly dense of Jayapura downtown area, which results to the problems of land use and the decrease of environment quality. Therefore, it is necessary to create green open spaces to reduce the environment impact. This paper aims to analyze the needs of green open spaces in Jayapura downtown by several variables: the percentage of land area, the number of population, and the need of oxygen. The findings showed the current green open spaces available are still below standard since only the city park has meet the requirement of minimum area. It should be efforts to solve this problem by revegetation and optimalizing the available lands as green open space, the use of green roof, and green living like providing bicycle lanes and pedestrian paths.
Keywords: land available; green open space; environment quality; Jayapura downtown